Pharmacoeconomic evaluation of treatment in patients with Helicobacter pylori-associated diseases - A A Samsonov; V B Grechushnikov; D N Andreev; G L Iurenev; T I Korovina; Iu A Lezhneva; I V Maev (Терапевтический архив, 2014)
AIM. To estimate the pharmacoeconomic parameters of treatment in patients with Helicobacter pylori-associated diseases when using 6 eradication therapy (ET) regimens. MATERIALS AND METHODS. The investigation enrolled a total of 231 patients who received anti-Helicobacter pylori therapy according to the intention-to-treat (ITT) principle, including 229 patients who met the protocol requirements, i.e. who completed the prescribed per-protocol (PP) treatment: 106 patients with duodenal bulb ulcer disease, 2 with gastric ulcer, 90 with erosive gastritis, and 31 patients with non-atrophic gastritis. In an outpatient setting, the patients received one of the 6 ET regimens: OAC, RBMA, RBCA, EBCA, sequential OACM therapy, and modified sequential OACMB therapy (O - omeprazole; A - amoxicillin; C - clarithromycin; B - bismuth tripotassium dicitrate, R - rabeprazole; M - metronidazole; E - esomeprazole). Treatment costs were calculated only from direct drug expenditures. The effective cost coefficient (Keff) was determined from the cost/treatment efficiency ratio: Keff=cos/eff, where the cost was the average total costs; the eff was efficiency (%). RESULTS. The modified sequential OACMB therapy has proven to be more cost-efficient than the other regimens as it has a lower Keff (14). The RBMA regimens can overcome an 80% ET barrier (82.4%); however, in this case the Keff is 21.5. the sequential OACM therapy can also overcome an 80% ET barrier (84.8%); the Keff being 10.8. Incorporation of the bismuth preparation can achieve a more noticeable therapeutic effect up to 95.4%. The EBCA regimen has turned out to be most expensive with the highest Keff of 36.9. The RBCA regimen is most effective with the least Keff of 29; the therapeutic effect is 96.7%. CONCLUSION. The clinical cost-efficiency of ET is enhanced by the incorporation of the bismuth preparation for the treatment of patients with H. pylori-associated diseases. The modified sequential OACMB therapy can overcome resistance to clarithromycin and metronidazole with a good cost-efficiency.